Effect of "Deqi" during the Study of Needling "Wang's Jiaji" Acupoints Treating Spasticity after Stroke. (12th November 2014) - Li, Huanqin; Liu, Huilin; Liu, Cunzhi; Shi, Guangxia; Zhou, Wei; Zhao, Chengmei; Zhang, Tao; Wang, Xuefei; Wang, Guiling; Zhao, Yin; Sun, Jingqing; Wang, Jing; et al.
Abstract : Background. Acupuncture has been shown to reduce spasticity and prevent the onset of spasticity after stroke. The purpose of this study is to assess the effect of "Deqi" during needling "Wang's Jiaji" acupoints treating spasticity in the early stage of stroke. Methods . This study is a multicenter, prospective, randomized, controlled trial. 238 patients with stroke (<21 days) participated and were randomly allocated to the verum-acupuncture (n = 121 ) group or sham-acupuncture group (n = 117 ). The verum-acupuncture group received verum acupuncture required to produce the sense of "Deqi" while the sham-acupuncture group received sham acupuncture without "Deqi." Patients in both groups followed the same 30 min acupuncture regimen 5 times per week for a period of 4 weeks. Scales of MAS, FMA, ADL, MBI, NIHSS, SS-QOL, and MRS were measured at baseline and at 2, 4, and 12 weeks after intervention. Results. Significant differences were observed between two groups. The MRS rating composition has the statistical difference after 4 weeks (P = 0.017 ). The score of MAS, FMA, Barthel, and SSQOL in verum-acupuncture group has increased significantly compared with the sham-acupuncture group after 12 weeks. There was 14% reduction of higher muscle tension in the verum-acupuncture group. Conclusion. Acupuncture "Wang's Jiaji" points with sensation of "Deqi" in the early stage may reduce the occurrence and decrease the severity of spasticity after stroke.